The Power of Food Science and Technology and Nutrition for Sustainable Planet Health: Food Processing Saves Lives - Fereidoon Shahidi (Journal of Food Bioactives, 2021)
Food processing includes a chain of events that starts in the farm and continues to the serving plate. These may include washing, dehydration, blanching, heat processing, and packaging, among others. While processing is essential for providing a safe food supply by eliminating harmful microorganisms and certain undesirable components, as well as revealing the desirable flavor of food, there has been much recent attempt to condemn food processing. Thus, loss of certain nutrients during processing and use of additives in ready to eat food as well as high levels of salt, sugar and fat/oil have been noted as being responsible for many non-communicable diseases due to increased incidence of obesity, diabetes and cardiovascular disease.  These have all been categorised as ultra-processed food but attention to the definitions and details is most important.